Utemeljena teorija v razvojnopsihološkem raziskovanju - Sedmak, Ana (Psihološka obzorja (Ljubljana), 2025)
The article presents findings from several years of research using grounded theory, a method of qualitative research in developmental psychology. As a qualitative method, grounded theory procedures are both defined and undefined. On the one hand, grounded theory involves strict guidelines for data collection, checking for data saturation, coding rules and the creation of categories at different levels of abstraction. On the other hand, a significant part of the decision making is left to the researchers, who are required to transparently document and report their research process. This article presents the challenges of using grounded theory as a research method in developmental psychology. We illustrate its procedures by a research project on YouTubers as an identification model in children and adolescents. Data were collected through interviews and focus groups with children, adolescents and parents. The findings provide a number of methodological insights into the challenges of grounded theory research in developmental psychology, and highlight practical considerations for its further application, including the development of new analytical tools using AI learning models.
Keywords: case study; grounded theory; kvalitativno raziskovanje; qualitative research; študija primera; utemeljena teorija; YouTuberji; YouTubers